Aerial photography and parcel mapping for immovable property registration in Albania - Gjika, Maksimiljan; Leka, Edmond; University of Wisconsin--Madison. Land Tenure Center.; Albania. Immovable Property Registration and Market Action Plan (Project). Project Management Unit. (Land Tenure Center, University of Wisconsin-Madison, 1997)
Planimetric map production is a basic graphic documentation element of the Immovable Property Registration System in Albania and is one of the main objectives of the Land Market Action Plan. This paper focuses on the implementation of photogrammetry program mapping of index maps for the registration system being developed for Albania. Photogrammetric work occupies an important place among the well-known methods of mapping. Methods for various types of map production based on aerial information are being developed. Analytical photogrammetry is completed theoretically, on an advanced technological base and with hands-on experience in all phases. At present, photogrammetry and remote sensing is changing from analog to digital, from aerial to space-based imaging/mapping, from local to global concepts, and from manually managed to computerized information systems such as the geographic information system. It is not always possible for technology to change from the old to the new. This depends on economic and financial possibilities, on existing technological bases, and, more importantly, on efficiency of the new technology to resolve the problem. In a lot of cases, analogical equipment has been adapted using various types of alterations in order to process as much information as possible and gradually to pass on to higher levels of technology. This paper examines the way aerial photography has been used for surveying in Albania.
iii, 10 p.
Keywords: Aerial photography in land use Albania; Land titles Registration and transfer Albania; Aerial photogrammetry Albania